Detection of Salmonella Javiana in taricaya turtles (Podocnemis unifilis) in two zoos in Peru - Campos N., Andrea (2020)
The aim of this study was to serotype and determine the antibacterial sensitivity profile of Salmonella spp strains isolated from taricaya turtles (Podocnemis unifilis) from the Huachipa Zoological Park (n = 30). Lima, and the Natural Park of Pucallpa (n = 43), Ucayali, located in the coastal and jungle region of Peru, respectively. A total of 73 samples of cloacal swabs were obtained that were inoculated in Stuart bacterial transport media, enrichment media (tetrathionate broth) and selective media (XLD agar and Salmonella-Shigella), finding typical lactose-negative colonies of Salmonella, which were verified by biochemical tests standard (4.11%, 3/73). The results of the serological typing using the Kauffmann-White scheme showed that two of the three strains corresponded to Salmonella Javiana (O9,12: I, Z28: H5) and the other as not determined. The three positive samples were from juvenile turtles, of indefinite sex and from one of the two centers under study. Antimicrobial sensitivity tests determined that the strains of S. Javiana were sensitive to streptomycin, trimetopim sulfamethoxazole, fosfomycin, furazolidone, gentamicin and chloramphenicol and resistant to enrofloxacin, and tetracycline.